Hubungan Antara Dukungan Keluarga dengan Work-Family Conflict Pada Polwan Di Polda Sumut - Wira Yudhistira Adiyatma Harahap; Babby Hasmayni (Tabularasa: Jurnal Ilmiah Magister Psikologi, 2022)
This study aims to empirically test and determine the relationship between family support and work-family conflict among female policewomen at the North Sumatra Regional Police. The sample used in this study were 45 female police officers from the general criminal directorate at the North Sumatra Police. The technique used by the researcher is purposive sampling technique. Family support in this study was measured based on aspects of family support. Work-family conflict in this study is measured by aspects. Where the higher the Work-family conflict score, the higher the Work-family conflict score, conversely, the lower the Work-family conflict score, the higher the Work-family conflict score. It can be seen that there is a negative relationship between family support and work-family conflict. This result is evidenced by the correlation coefficient rxy = -0.771, with significant p = 0.000 0.05. The determinant coefficient (r2)= 0,595. This shows that social support is distributed by 59.5%% of Work-family Conflict. Based on the results of the calculation of the hypothetical and empirical mean values, it can be concluded that family support is low with a hypothetical mean value of 57.5 and an empirical mean of 45.27. Furthermore, it can be concluded that Work-family Conflict is classified as high with a hypothetical value of 100 and an empirical value of 118.84.